Studi komparatif kurikulum pendidikan di beberapa negara maju sebagai rujukan di Indonesia - AUFAQIL, HIMAWAN; Shabrina, Shabrina; Riski, Dinda Dwi (Maliki Interdisciplinary Journal, 2025)
This study examines a comparative analysis of curriculum systems in several developed countries—Finland, Japan, the United States, and Singapore—with the aim of identifying insights and best practices that can be adapted for curriculum development in Indonesia. The background of this research lies in the crucial role of the curriculum as a primary guideline determining the direction, content, and quality of learning within educational institutions. This study employs a library research method by analyzing relevant literature and previous studies related to the curriculum systems of each country. The findings reveal that Finland emphasizes equality and student well-being, Japan focuses on character and moral development, the United States highlights flexibility and decentralization, while Singapore stands out in academic excellence and bilingual education. Each model presents its own strengths and challenges that can serve as valuable references in designing a national curriculum that is adaptive, humanistic, and relevant to the educational demands of the 21st century.